2009
DOI: 10.1111/j.1601-0825.2009.01531.x
|View full text |Cite
|
Sign up to set email alerts
|

The minor salivary gland proteome in Sjögren’s syndrome

Abstract: We have identified several minor salivary gland proteins that may have implications for clarifying the SS pathophysiology. This experiment adds to the knowledge of proteins produced in salivary glands in health and disease, and may form the basis of further studies on biomarkers of prognostic and diagnostic value.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 56 publications
(87 reference statements)
0
18
0
1
Order By: Relevance
“…We observed down regulation of Ig J in all types of DES associated with non Sjogrens, primary and secondary to RA. Studies showed down regulation of Ig J chain in salivary gland tissue of primary SS cases using proteomic approach after treatment with the steroids [37], [38]. Further quantification in tear would help in ascertaining the role in inflammation seen in DES especially before and after treatment.…”
Section: Discussionmentioning
confidence: 99%
“…We observed down regulation of Ig J in all types of DES associated with non Sjogrens, primary and secondary to RA. Studies showed down regulation of Ig J chain in salivary gland tissue of primary SS cases using proteomic approach after treatment with the steroids [37], [38]. Further quantification in tear would help in ascertaining the role in inflammation seen in DES especially before and after treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The salivary glands broadly express proteins that may be modified by PAD, including vimentin, enolase, and others [2123]. Furthermore, the salivary glands constitutively express PAD2, and this enzyme may convert arginine residues into citrulline, which is the cornerstone of the citrullination process.…”
Section: Discussionmentioning
confidence: 99%
“…Проте-омный состав слюнных желез больных синдромом Шегре-на (СШ) характеризовался гиперэкспрессией таких бел-ков, как β-актин, α-дефенсин, кальмодулин, кальгранулин и кератин. Повышенный уровень последнего ассоцииро-вался с поражением ацинозных клеток, а содержание каль-модулина и кальгранулина отражало активность воспали-тельного процесса [76]. У пациентов с остеоартрозом (ОА) в хондроцитах хряща при помощи 2D-гель-электрофореза и MS было идентифицировано 20 белковых кандидатных маркеров заболевания.…”
Section: поиск биомаркеров ревматических заболеванийunclassified